2013
DOI: 10.1177/1932202x12472602
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Apples and Oranges

Abstract: The lack of a unified definition of giftedness leads researchers to use very different operationalizations when selecting a sample of gifted individuals for use in research. We found 104 empirical articles from 38 journals that differentiated between gifted and nongifted students which were analyzed to determine the most common methods of identifying individuals in research. Results of the analysis show a lack of consensus as to what qualifies a person to be defined as gifted for the purposes of research. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 111 publications
(153 reference statements)
0
41
0
3
Order By: Relevance
“…Congruence between pairs of tests in the detection of high-ability students was also established. Although considering an IQ of 130 or above – or two typical deviations above the average – seems to be an arbitrary criterion, in both research and educational practice this criterion is still used, in most cases, as a cut-off point to determine which students have higher intellectual abilities (Moon and Brighton, 2008; Carman, 2013; Guignard et al, 2016; Peyre et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Congruence between pairs of tests in the detection of high-ability students was also established. Although considering an IQ of 130 or above – or two typical deviations above the average – seems to be an arbitrary criterion, in both research and educational practice this criterion is still used, in most cases, as a cut-off point to determine which students have higher intellectual abilities (Moon and Brighton, 2008; Carman, 2013; Guignard et al, 2016; Peyre et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, although the exclusive use of standardized tests to assess intellectual ability has its detractors (Pfeiffer, 2012) and these tests are not the only measures available nowadays, the fact remains that standardized tests have been accepted as reliable measures of identifying students with higher abilities to date (Lovett and Lewandowski, 2006; Lovett and Sparks, 2011; Erwin and Worrell, 2012) and as Carman (2013) suggests “no matter how often researchers suggest that an IQ score is not the only way of determining giftedness, it is still the most common method of identifying gifted participants for research, either alone or in combination with other criteria.” At a practical level, in Spain the information obtained from standardized tests is the first criterion used to determine if a student may have higher abilities, and is essential for continuation of the evaluation process. This measure is used as a baseline analysis of the students’ capacities and offers a starting point for the detection of higher intellectual abilities (Renzulli, 2012; Wellisch and Brown, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been defined in terms of high intelligence, creativity, high school performance, leadership, task commitment, and higher likelihood of attaining significant achievements in culturally valued domains (Fernández et al 2017;Peyre et al 2016;Pfeiffer 2012;Renzulli 1978). Despite the lack of consensus, most experts generally agree that a hallmark of giftedness is high intelligence (Carman 2013;Marland 1972), Even so, there is no consensus on what level of intelligence constitutes giftedness (Rommelse et al 2015). Intelligence quotient (IQ), the traditional indicator of an individual's intelligence, is generally established by a well standardized IQ test.…”
Section: Giftednessmentioning
confidence: 99%
“…Other popular methods of identifying gifted children were nominations and referrals (71%), intelligence test scores (66%), multiple criteria (64%), a "range of approved assessments" (50%), and grades (32%;Education Week Research Center, 2019, p. 12). In another show of the diversity of operationalizations of giftedness, Carman's (2013) found that 62.0% of gifted education studies reported that a group of gifted children were identified by a score equal to or above a cutoff on an intelligence test, while achievement test scores (34.8% of studies) and prior academic achievement (23.9% of studies)…”
Section: Beliefs About Human Intelligence From a Sample Of Teachers Amentioning
confidence: 99%